Budaya Tradisi Sebagai Kekuatan Komunitas Adat Terpencil - Marisa Elsera; Oksep Adhayanto (Jurnal Archipelago, 2022)
Traditional values that are still preserved and binding on Indigenous Communities are often regarded as one of the obstacles to modernism by the modernization stream. Indigenous is still viewed by indigenous people as a social problem, because its alienation & backwardness make them a socially vulnerable group (socio-political silliness). Even in the Regulation of the Minister of Social Affairs Number 8 of 2012, it has stipulated KAT as one of the 26 Persons with Social Welfare Problems (PMKS) in Indonesia. This research discusses traditional culture as the strength of KAT. Based on this research, it was found that traditional culture plays a positive role in encouraging development for the Sea Tribe community itself. The traditional elements owned by the Sea Tribe community and can be a force in supporting development, namely; first, the collective consciousness awakened in the people of the Sea Tribe to protect nature. Second, responsibility to family, community and tribalism is great when compared to a more individualistic modern society. Third, the animist belief of the Sea Tribe people who still believe that a person who always does evil during his life and then dies, his spirit will be incarnated in the form of an animal that comes out of his grave. Fourth, the role of religious leaders for the Orang Laut community in the Riau Islands is a force to encourage development in the Sea Tribe community, especially as a bridge of communication with local governments. Fifth, the presence of Sea Tribe shamans who are trusted by some local Malay communities makes the presence of the Sea Tribe community acceptable and can gradually blend into the local community.